PENGARUH PENERAPAN SISTEM INFORMASI PENGELOLAAN KEUANGAN DAERAH (SIPKD) TERHADAP KUALITAS LAPORAN KEUANGAN PADA BADAN KEUANGAN DAERAH SETDA PEMERINTAH PROVINSI NUSA TENGGARA TIMUR - Martha Nathasya Lotu (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
This research was conducted at the Office of the Regional Finance Agency of East Nusa Tenggara. The purpose of this study was to determine the effect of the implementation of the Regional Financial Management Information System (SIPKD) on the quality of local government financial reports at the Regional Finance Agency of East Nusa Tenggara Province partially. The number of samples in this study were 43 who were staff who were directly involved in the implementation of SIPKD, the researchers took samples using the purposive sampling method. Data collection techniques in this study using a questionnaire. The data analysis technique in this study used simple linear regression analysis. Based on the results of the partial analysis, it is known that the Regional Financial Management Information System (SIPKD) affects the quality of financial reports with a coefficient of determination of 15% while the other 85% is influenced by other factors.